Why Linguistics? - Robert K. Rasmussen (Washington University Law Quarterly, 1995)
The question I pose for those who have devoted considerable effort to the project is why linguistics should have anything to offer those who would interpret legal texts. An answer to the question requires both an understanding of what linguistics is and a theory for why it might illuminate areas of interest for us. Through the materials of the symposium I believe I have acquired a reasonably accurate, if limited, understanding of the linguist's enterprise, but nowhere in the materials have I found help with the theoretical problem.
Keywords: Linguistics